Diverse mechanisms associated with cyhalofop-butyl resistance in Chinese sprangletop (Leptochloa chinensis (L.) Nees): Characterization of target-site mutations and metabolic resistance-related genes in two resistant populations - Zhang, Yi; Chen, Liping; Song, Wen; Cang, Tao; Xu, Mingfei; Wu, Changxing (Frontiers in Plant Science, 2022)
Resistance of Chinese sprangletop (Leptochloa chinensis (L.) Nees) to the herbicide cyhalofop-butyl has recently become a severe problem in rice cultivation. However, the molecular mechanisms of target-site resistance (TSR) in cyhalofop-butyl-resistant L. chinensis as well as the underlying non-target-site resistance (NTSR) have not yet been well-characterized. This study aimed to investigate cyhalofop-butyl resistance mechanisms using one susceptible population (LC-S) and two resistant populations (LC-1701 and LC-1704) of L. chinensis. We analyzed two gene copies encoding the entire carboxyltransferase (CT) domain of chloroplastic acetyl-CoA carboxylase (ACCase) from each population. Two non-synonymous substitutions were detected in the resistant L. chinensis populations (Trp2027-Cys in the ACCase1 of LC-1701 and Leu1818-Phe in the ACCase2 of LC-1704), which were absent in LC-S. As Trp2027-Cys confers resistance to ACCase-inhibiting herbicides, the potential relationship between the novel Leu1818-Phe mutation and cyhalofop-butyl resistance in LC-1704 was further explored by single-nucleotide polymorphism (SNP) detection. Metabolic inhibition assays indicated that cytochrome P450 monooxygenases (P450s) and glutathione S-transferases (GSTs) contributed to cyhalofop-butyl resistance in specific resistant populations. RNA sequencing showed that the P450 genes CYP71Z18, CYP71C4, CYP71C1, CYP81Q32, and CYP76B6 and the GST genes GSTF11, GSTF1, and GSTU6 were upregulated in at least one resistant population, which indicated their putative roles in cyhalofop-butyl resistance of L. chinensis. Correlation analyses revealed that the constitutive or inducible expression patterns of CYP71C4, CYP71C1, GSTF1, and GSTU6 in L. chinensis were strongly associated with the resistant phenotype. For this reason, attention should be directed towards these genes to elucidate metabolic resistance to cyhalofop-butyl in L. chinensis. The findings of this study improve the understanding of mechanisms responsible for resistance to ACCase-inhibiting herbicides in grass-weed species at the molecular level, thus aiding in the development of weed management strategies that delay the emergence of resistance to this class of pest control products.